Giant Dermatofibroma: A Rare Presentation as a Large Scaly Plaque - T. Iqbal; V. Mudaliar (Case Reports in Dermatological Medicine)
A rare form of dermatofibroma (DF) is described in the literature as giant dermatofibroma. Due to the rarity and distinct presentation that can be confused with more sinister skin tumours, these can cause diagnostic uncertainty and require clinicopathologic correlation. Familiarity with this rare presentation of an otherwise common entity is required to prevent unnecessary clinical doubt and excessive interventions. We report a case of giant dermatofibroma on the leg of a 29-year-old healthy male that presented with a 7 cm, nonulcerated pink, brown plaque, adding to the limited literature of less than 30 known cases.